The Empty Spain from a humanistic perspective: Intersections between El Cielo gira and the essays on depopulation - García-Cardona, Juan; España Arjona, Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims to investigate the treatment of Empty Spain; while this issue has been widely addressed by the social sciences, the potential work of the humanities in reversing this process of depopulation has not been taken into account. El cielo gira, a documentary by Mercedes Álvarez, is about the last inhabitants of Aldealseñor, a village in Soria on the verge of extinction. In addition to offering a novel approach to the problem of rural abandonment, Álvarez’s documentary has turned Aldealseñor into an internationally recognized village that has attracted viewers from all over the world.